Coronary Computed Tomography Angiography–Specific Definitions of High-Risk Plaque Features Improve Detection of Acute Coronary Syndrome: Results From the ROMICAT II Trial. (August 2018) - Bittner, Daniel O.; Mayrhofer, Thomas; Puchner, Stefan B.; Lu, Michael T.; Maurovich-Horvat, Pal; Ghemigian, Khristine; Kitslaar, Pieter H.; Broersen, Alexander; Bamberg, Fabian; Truong, Quynh A.; Schlett, Christopher L.; Hoffmann, Udo; et al.
Abstract : Background: High-risk plaque (HRP) features as detected by coronary computed tomography angiography (CTA) predict acute coronary syndrome (ACS). We sought to determine whether coronary CTA-specific definitions of HRP improve discrimination of patients with ACS as compared with definitions from intravascular ultrasound (IVUS). Methods and Results: In patients with suspected ACS, randomized to coronary CTA in the ROMICAT II (Rule Out Myocardial Infarction/Ischemia Using Computer Assisted Tomography II) trial, we retrospectively performed semiautomated quantitative analysis of HRP (including remodeling index, plaque burden as derived by plaque area, low computed tomography attenuation plaque volume) and degree of luminal stenosis and analyzed the performance of traditional IVUS thresholds to detect ACS. Furthermore, we derived CTA-specific thresholds in patients with ACS to detect culprit lesions and applied those to all patients to calculate the discriminatory ability to detect ACS in comparison to IVUS thresholds. Of 472 patients, 255 patients (56±7.8 years; 63% men) had coronary plaque. In 32 patients (6.8%) with ACS, culprit plaques (n=35) differed from nonculprit plaques (n=172) with significantly greater values for all HRP features except minimal luminal area (significantly lower; all P <0.01). IVUS definitions showed good performance while minimal luminal area (odds ratio: 6.82; P =0.014) and plaque burden (odds ratio: 5.71; P =0.008) were independently associated with ACS but not remodeling index (odds ratio: 0.78; P =0.673). Optimized CTA-specific thresholds for plaque burden (area under the curve: 0.832 versus 0.676) and degree of stenosis (area under the curve: 0.826 versus 0.721) showed significantly higher diagnostic performance for ACS as compared with IVUS-based thresholds (all P <0.05) with borderline significance for minimal luminal area (area under the curve: 0.817 versus 0.742; P =0.066). Conclusions: CTA-specific definitions of HRP features may improve the discrimination of patients with ACS as compared with IVUS-based definitions. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01084239 Abstract : Supplemental Digital Content is available in the text.